2019
DOI: 10.1002/cpt.1588
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib Activity and Disposition in Liver Cancer Does Not Depend on Organic Cation Transporter 1

Abstract: Systemic therapy of advanced hepatocellular carcinoma (HCC) with the small molecule multikinase inhibitor sorafenib is associated with large inter-individual pharmacokinetic variability and unpredictable side effects potentially requiring dose reduction or treatment termination. Organic cation transporter OCT1 (gene SLC22A1) has been proposed as clinical biomarker of HCC response. Because proof is lacking that OCT1 transports sorafenib, we used a combinatorial approach to define how OCT1 contributes to sorafen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Solute carriers (SLC) play an essential role in the uptake of anticancer drugs. For instance, although a controversial study has reported the inability of organic cation transporter-1 (OCT1, SLC22A1 ) to transport sorafenib [ 8 ], others using Xenopus laevis oocytes and mammalian cells with stable expression of OCT1 have revealed that this transporter is involved in the uptake of sorafenib [ 9 , 10 ], but not regorafenib [ 10 ]. Reduced SLC22A1 expression and impaired OCT1 function, due to loss-of-function mutations and aberrantly spliced variants in HCC, have been reported ( Table 1 ) [ 9 , 10 ].…”
Section: Drug Uptake and Export (Moc-1)mentioning
confidence: 99%
“…Solute carriers (SLC) play an essential role in the uptake of anticancer drugs. For instance, although a controversial study has reported the inability of organic cation transporter-1 (OCT1, SLC22A1 ) to transport sorafenib [ 8 ], others using Xenopus laevis oocytes and mammalian cells with stable expression of OCT1 have revealed that this transporter is involved in the uptake of sorafenib [ 9 , 10 ], but not regorafenib [ 10 ]. Reduced SLC22A1 expression and impaired OCT1 function, due to loss-of-function mutations and aberrantly spliced variants in HCC, have been reported ( Table 1 ) [ 9 , 10 ].…”
Section: Drug Uptake and Export (Moc-1)mentioning
confidence: 99%
“…A 10% dimethyl sulfoxide (DMSO) stock for sorafenib tosylate and 0.9% sodium chloride for atoravastatin and metformin were used to prepare the drug solutions. Blood samples were collected before administration and after dosing at the following time points: 0.5, 1, 2, 3, 4, 5,6,7,8,10,12,24,30,48,72, and 96 h (for sorafenib); 0.083, 0.25, 0.5, 0.75, 1, 2, 4, 6, and 12 h (for atorvastatin); and 0.083, 0.25, 0.5, 1, 1,5, 2, 4, 6, 8, 10, and 24 h (for metformin). The plasma was separated by centrifugation at 2880× g for 10 min at 4 • C and stored at −80 • C until drug analysis.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…sodium hydroxide 3 67-56-1 sodium hydroxide microprills 5 1310-73-2 sorafenib 6 284461-73-0 sorafenib N-oxide 6 583840-03 rosuvastatin calcium 3 147098-20-2 ultrapure water (deionized, distilled, and filtered through Direct Q3 system) 4 7732-18-5 1 purchased from CHEMPUR (PiekaryŚląskie, Poland); 2 purchased from Santa Cruz Biotechnology, Inc. (Dallas, TX, USA); 3 purchased from Sigma-Aldrich (Saint Louis, MO, USA); 4 purchased from Merck Millipore (Burlington, MA, USA); 5 purchased from POCH S.A. (Gliwice, Poland); 6 purchased from LGC (Teddington TW11 0LY, UK).…”
Section: Reagent Cas Numbermentioning
confidence: 99%
“…Several studies indicated the importance of the member 22 of the solute carrier family (organic cation/anion transporter) in sorafenib resistance. SLC22A1 (OCT1) has been reported to be involved in the uptake of sorafenib, both in an animal model or human cells [53,54], even though a recent study showed opposing results [55]. Downregulation of OCT1 and OCT3 (SLC22A3) was observed in HCC [56,57] which was further associated with a poor survival in patients treated with sorafenib, independently from the clinical staging of the associated liver disease [58].…”
Section: Drug Uptake: the Slc Familymentioning
confidence: 99%